Evaluation of microbial consortium for rapid composting of rice straw - Kaur, Tamanraj (My University, 2018)
Present research work was aimed at developing a system for rapid composting of agriculture wastes such as rice straw for its applications as soil amendment to improve plant growth. Out of 19 bacterial isolates from the rhizospheric soil of rice straw, seven bacterial isolates were found to be Gram positive, four were positive for methyl red test, 17 were starch hydrolysis positive, only two were Voges-Proskauer positive. Nine bacterial isolates were found to be cellulose degrading bacteria. Composting of rice straw with a consortium of fast degrading microbes was also done. Rice straw was collected from Devigarh, Patiala. Composting of rice straw was done in plastic beakers using a consortium of microbes, comprising Bacillus subtilis (NA 15), Paenibacillus polymyxa, Saccharomyces cerevisiae and Trichoderma reesei (MTCC 164) with and without fertilizer (DAP- diammonium phosphate) treatment. Various parameters such as pH, temperature, organic carbon, nitrogen, reducing sugar and cellulose content were monitored at different intervals for 60 days. Organic carbon content for rice straw was recorded as 69.1% in case of control and it dropped to 40%, In case of consortium it was recorded as 69.1% and it dropped to 30.2%, In case of consortium + fertilizer it was recorded as 69.1% and it dropped to 25% and in case of fertilizer only it was recorded as 69.1% and it dropped to 29% from 0 day to 60th day of observation. The nitrogen content showed increasing trend from 0.063% on 0 day to 2.0% on 60th day when treatment with microbial consortia was given to the rice straw, When consortia + fertilizer treatment was given it the increase was observed from 0.063% to 2.3%, In case of fertilizer only the increase in nitrogen was observed from 0.063% to 2.1% while in case of control it was increased from 0.063% to 1.42%. Simultaneously, there was a drop in C: N ratio was observed from 1096.8 to 28.23 in case of control, When treatment with microbial consortia was given to rice straw it got reduced from 1096.8 to 14.51, In case of consortium + fertilizer it reduced from 1096.8 to 10.91 and in fertilizer only it reduced from 1096.8 to 13.85 from 0 day to 60th day of observation. Loss in moisture content was from 60.2% to 41.1% over the period of 60 days. Reducing sugar yield was observed to have an increasing trend from 0.91 mg/ml on 7th day to 2.0 mg/ml on 60th day when treatment with microbial consortia was given to the rice straw, when consortia + fertilizer treatment was given it the increase was observed from 1.06 mg/ml to 2.3 mg/ml, in case of only fertilizer the increase in reducing sugar was observed from 0.91 mg/ml to 1.9 mg/ml while in case of control the reducing sugar increased from 0.3 mg/ml to 1.11 mg/ml. The total weight of biomass got reduced as a result of microbial degradation. There was gradual decline in cellulose content however rapid decline was observed in rice straw treated with consortia and fertilizer. Treatment with consortium + fertilizer was the best among all that could reduce the period of composting almost from 60 days to 30 days. This treatment can be used for large scale recycling of rice straw.
Keywords: biodegradation; bacterial isolates; fertilizer; cellulose dependeny; rice straw